Weight Loss Changed Gait Kinematics in Individuals with Obesity and Knee Pain - Li, Jing-Sheng (Gait Posture, 2018)
BACKGROUND: Obesity is a mechanical risk factor for osteoarthritis. In individuals with obesity, knee joint pain is prevalent. Weight loss reduces joint loads, and therefore potentially delays disease progression; however, how the knee joint responds to weight loss in individuals with obesity and knee pain is not clear. RESEARCH QUESTION: To assess the effect of weight loss on knee joint kinematics during gait in individuals with obesity and knee pain. METHODS: We recruited individuals with obesity (BMI ≥ 35) and knee pain who were participating in a weight loss program which included bariatric surgery or medical management. At baseline before and at 1 year after treatment, participants walked on a treadmill, and their knee joint kinematics were assessed using a dual-fluoroscopic imaging system and subject-specific magnetic resonance imaging knee joint models. Gait changes were represented by change in range of tibiofemoral motion, i.e., excursions in flexion-extension, adduction-abduction, internal-external rotation, anterior-posterior translation, medial-lateral translation, and superior-inferior translation during gait. RESULTS: Twelve individuals with obesity and knee pain completed the gait analysis at baseline and 1 year follow-up. Participants lost on average 10.4 % (standard deviation: 17.2%) of their baseline body weight. Reduction in body weight was associated with increased range of flexion-extension (r = −0.75, p < 0.01) and decreased range of adduction-abduction (r = 0.60, p = 0.04) during gait. The reduction in body weight was also associated with self-reported pain decrease (r= 0.62, p = 0.04); however, the change in pain was not significantly associated with kinematic changes. SIGNIFICANCE: Weight loss was associated with improved gait kinematics in the sagittal and frontal planes. The change in gait pattern in individuals with obesity and knee pain was not associated with the change in pain given a reduction in body weight.